Diáspora, violencia y deseo: borrado y recuperación de la memoria charnega - Alba Solà García (Mélanges de la Casa de Velázquez, 2024)
In this article we will work on the figures, imaginaries and collective memory of the Charnego in the work of Juan Marsé. Emerging from the waves of migration to the Catalan capital during Franco’s dictatorship, this word designated in a pejorative fashion the new generations resulting from the rural diaspora, marking a subaltern, peasant and class origin, which was extended to the inhabitants of the urban and working-class peripheries of the city of Barcelona. The Charnego is thus located in a liminal and, at the same time, exogenous place, which contains a dimension that is both material and symbolic: the violence exercised on their bodies and their disposability on the margins of the city produces a symbolic world (a different culture, language, epistemology and ways of life), generating a place of dissident enunciation that questions and weakens the hegemonic narrative celebrating modernisation and progress, disseminated by the regime and capitalist teleology and further extended with the arrival of democracy. The Charnego memory, containing multiple layers of violence (peasant dispossession, urban exploitation and marginalisation, class subalternity) articulates another memory, political and historical, of the city and the past. Marsé, an adopted son of Guinardó, transposes the Charnego question into his narrative in many of his novels, issues and characters. Based on cultural criticism, the coloniality of power and urban and memory studies, we will analyse several works by Marsé, which we will relate to contemporary and later works by the author, in order to rethink two fundamental axes in the articulation of the Charnego in literature. On the one hand, territoriality and urban space, and, on the other, the production of narrative, identity and memory. The fact that the concept fell into disuse with the reconfiguration of the cultural, economic and political field of the transition to democracy (1975-1992) stripped the signifier of its memory; dehistoricising it: and despite this, as we shall see, the Charnego contains a revulsive charge that demands, today, its repoliticisation and its right to recover its place in the collective memory of the recent peninsular past.